The Primacy of Maternal Innovations to the Evolution of Embryo Implantation. (11th June 2020) - Stadtmauer, Daniel J; Wagner, Günter P
Synopsis: Embryo implantation is a hallmark of the female reproductive biology of eutherian (placental) mammals and does not exist in a sustainable form in any other vertebrate group. Implantation is the initial process that leads to a sustained fetal-maternal unit engendering a complex functional relationship between the mother and the embryo/fetus. The nature of this relationship is often portrayed as one of conflict between an aggressive embryo and a passive or defensive maternal organism. Recent progress in elucidating the evolutionary origin of eutherian pregnancy leads to a different picture. The emerging scenario suggests that the very initial stages in the evolution of embryo implantation required evolutionary changes to the maternal physiology which modified an ancestral generic mucosal inflammation in response to the presence of the embryo into an active embedding process. This "female-first" evolutionary scenario also explains the role of endometrial receptivity in human pregnancy. On the marsupial side, where in most animals the fetal–maternal interaction is short and does not lead to a long term sustainable placentation, the relationship is mutual. In these mammals, uterine inflammation is followed by parturition in short order. The inflammatory signaling pathways, however, are cooperative, i.e., they are performed by both the fetus and the mother and therefore we call this relationship "cooperative inflammation." Based on these discoveries we reconceive the narrative of the maternal–fetal relationship.